Gallbladder Empyema: A Dreadly Complication of Acute Cholecystitis - Dinda Puspita Sari; Elvienna Shaffiranisa; Amrullah Muliawan Hamdin; Clara Nadila; Philip Habib (Jurnal Biologi Tropis, 2023)
Gallbladder empyema is a severe form of acute cholecystitis with additional suppuration with an incidence rate of 6.3%-26.6% and a mortality rate 3%. If not treated promptly, gallbladder empyema can cause complications. Therefore, in this literature review we will discuss gallbladder empyema in more depth and the immediate treatment that must be carried out to avoid complications in patients. In this literature review Schoolar, we conducted a search on the PubMed and Sciencedirect database    using    the search keyword “gallbladder empyema”, “empyema”, and “gallbladder”. Gallbladder empyema can occur due to bile that cannot be excreted from the gallbladder will cause infection from microorganisms so that the gallbladder becomes full of exudative material in the form of pus, causing acute inflammation. Diagnosis of gallbladder empyema can be done using Ultrasonography and Computed Tomography Scan (CT Scan). Percutaneous transhepatic gallbladder drainage (PTGBD) is a procedure for the initial management of gallbladder empyema before laparoscopic cholecystectomy. If gallbladder empyema is treated immediately, the prognosis is good. If not treated promptly, gallbladder empyema can lead to peritonitis, and bacteremia leading to a rapid systemic inflammatory response, shock, and sepsis.